Brand Reputation on Brand Performance in Surplus Indonesia - Yuliana, Lingga; Apriyana, Nurliya; Perkasa, Didin Hikmah; Waty, Sully Sia; Masnia, Masnia; Pratama, Aldiwa; Maria, Nadiya Tristi (Universitas Bina Sarana Informatika, 2024)
The research presented here uses the Indonesian Surplus case study to examine how brand reputation affects brand performance. The study employed a quantitative descriptive methodology with one hundred respondents—a proportion of men and women—dispersed around Jakarta. Using the Surplus Indonesia application, respondents who have bought goods from partners throughout the research period of July to December 2023 are the target audience for purposive sampling. Partial Least Square is used in the data analysis approach (PLS). Smart PLS version 4 was the data analysis tool that was implemented. Questionnaires in the form of Google Forms were distributed to respondents using a Likert scale with a range of one to five. The study's findings demonstrate that brand reputation significantly and positively affects brand performance. The research's management conclusion is that Surplus Indonesia's existence can function as a platform to assist small, medium, and large enterprises in the economy in managing food that is fit for human consumption.